How Language Learner Identity Can Be a Helpful Construct in Language Learning and Teaching - Yunita Rahmasari; Nurmi Nonci (International Journal in Applied Linguistics of Parahikma, 2021)
The interest in learner identity within the field of second and foreign language acquisition has been garnering increased attention. This increase can be understood due to the shift from the dominance of psycholinguistic approach to a greater demand for including socio-anthropological dimensions in the field of second language acquisition (SLA). In SLA, the relationship between learner identity and language learning can provide the field with a more comprehensive theory on the link between learners and the larger social world and how it can accommodate the learner’s language learning. Accordingly, this paper looks for how language learner identity is constructed through language learning and how it can eventually benefit the practice of language teaching and learning.